Signal integration challenges in African epidemic intelligence: Lessons from the 2026 Bundibugyo virus disease outbreak and application of the PREIS framework - Hyacinthe R. Zabre (Journal of Public Health in Africa, 2026)
On 17 May 2026, the Director-General of the World Health Organization determined that Ebola disease caused by Bundibugyo virus in the Democratic Republic of the Congo (DRC) and Uganda constituted a Public Health Emergency of International Concern. Ten days separated the initial alert (05 May) from laboratory confirmation (15 May) although multiple non-laboratory signals were already active. Using this outbreak, we argue that Africa’s principal detection challenge is often not signal availability but the timely interpretive integration of concurrent multi-source signals, and we outline how a reproducible analytical layer – the Pan-African Real-time Epidemiological Intelligence System (PREIS) framework – might support it.